POTRET KINERJA PEMERINTAH DESA SEULALAH BARU KOTA LANGSA DALAM MENGELOLA KEUANGAN DESA - Rambe, Sri Wulandari; Septiani, Putri (AKRUAL : Jurnal Akuntansi dan Keuangan, 2025)
This study aims to present a portrait of the performance of the Seulalah Baru Village Government, Langsa City, in village financial management. The research employed a descriptive method with a qualitative approach, utilizing observation, interviews, and document analysis for data collection. The findings indicate that the performance of village officials is considered good, particularly in terms of responsiveness and cooperation among village apparatus and community participation. Fund management is carried out through participatory planning via village deliberations, budget implementation aligned with development priorities, and transparent supervision by both internal bodies and the community. Overall, the village financial management complies with prevailing laws and regulations and has positively contributed to village development and community empowerment. Nevertheless, there remains a need to enhance the quality of supervision to achieve more optimal and sustainable village financial governance.